Upaya Meningkatkan Motivasi Belajar Siswa Sekolah Menengah Atas melalui Layanan Bimbingan Kelompok Berbasis Teknologi - Resti Patinggi; Sri Mulyati; Utari Sanda Pare; Resky Wilfa B; Tius Kogoya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Learning motivation is very important for students’ academic success, especially at the senior high school level. At SMA Negeri 3 Tana Toraja, there are still problems that cause low student motivation. These problems include lack of interest in learning, low self-confidence, and the use of technology mostly for entertainment purposes. This study aims to identify ways to improve students’ learning motivation through technology-based group guidance services. The research uses a library study method by collecting and analyzing scientific sources such as books and previous research journals. The results show that learning motivation is influenced by both internal and external factors. Internal factors include self-efficacy, while external factors include the fulfillment of needs for autonomy, competence, and social relatedness. Technology-based group guidance services can be an effective alternative because they combine social interaction with digital media that are familiar to students. Through discussions, sharing experiences, and the use of digital platforms, students become more active, open, and motivated in learning. Guidance and counseling teachers play an important role as facilitators in creating a supportive group dynamic. They provide positive reinforcement and help students develop self-confidence. Healthy group dynamics encourage supportive interactions, which in turn enhance students’ intrinsic motivation. Therefore, the integration of group guidance services and technology can be an effective strategy to improve students’ learning motivation and support optimal learning outcomes.